2017
DOI: 10.1016/j.matbio.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Decorin and biglycan are necessary for maintaining collagen fibril structure, fiber realignment, and mechanical properties of mature tendons

Abstract: The small leucine-rich proteoglycans (SLRPs), decorin and biglycan, are key regulators of collagen fibril and matrix assembly. The goal of this work was to elucidate the roles of decorin and biglycan in tendon homeostasis. Our central hypothesis is that decorin and biglycan expression in the mature tendon would be critical for the maintenance of the structural and mechanical properties of healthy tendons. Defining the function(s) of these SLRPs in tendon homeostasis requires that effects in the mature tendon b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
165
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(175 citation statements)
references
References 40 publications
8
165
2
Order By: Relevance
“…Could the absence of some of these ECM components compromise the biomechanical properties of tendon independent of collagen fibril alterations and could the observed alteration in collagen fibril diameters represent a generic physiological response to (re)adjust the biomechanical properties of tendon? Temporally controlled conditional deletions of these ECM components would address at which stage these proteins are required for tendon homeostasis and such studies already revealed distinct postnatal functions for biglycan and decorin . Lineage tracing experiments over the past several years made it abundantly clear that tendon tissue is host to more than one cell type .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Could the absence of some of these ECM components compromise the biomechanical properties of tendon independent of collagen fibril alterations and could the observed alteration in collagen fibril diameters represent a generic physiological response to (re)adjust the biomechanical properties of tendon? Temporally controlled conditional deletions of these ECM components would address at which stage these proteins are required for tendon homeostasis and such studies already revealed distinct postnatal functions for biglycan and decorin . Lineage tracing experiments over the past several years made it abundantly clear that tendon tissue is host to more than one cell type .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other biomechanical roles for the GAG‐containing proteins in tendon have been proposed, such as the distribution of transverse loads, and contribution to ultimate failure strength or creep/fatigue recovery. In support of biomechanical roles for GAGs and proteoglycans in tendon other than stretch recovery, more recent studies showed, that tendon from decorin knockout mice had decreased tendon viscoelasticity without affecting the elastic properties of tendon . The exact role for each of the SLRPs and other GAGs and glycoproteins and their cooperative interactions in tendon development and tendon function needs to be further investigated.…”
Section: Ecm Proteins Involved In Collagen Fibrillogenesis and Fibrilmentioning
confidence: 99%
“…The literature shows a modulatory action of fibromodulin, and especially of decorin, on collagen fibrillogenesis and, consequently, on the formation of the final diameter of the fibrils (Robinson et al ., ). The decorin, linked to a triple helix of collagen, seems to have an important role in the formation of the arrangement of molecules within these microfibrils, preventing their lateral fusion (Weber et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Robinson et al . () demonstrated the importance of biglycan and decorin for the collagen fibril structure and mechanical properties of mature tendons. In another study of our group, Nakagaki et al .…”
Section: Discussionmentioning
confidence: 97%
“…Bars: 200 ÎŒm realignment of the fibres, as well as the mechanical properties of the tendons 43. Chhabra et al 42 used knockout mice for the Gdf5 gene and observed calcaneus tendon repair delay, since the mutant animals presented less proteoglycans and collagen, as well as less organization of the collagen fibres.…”
mentioning
confidence: 99%